Adherence of hypertension patients in the Brazil’s Family Health Strategy - Anderson da Silva Rêgo; Cremilde Aparecida Trindade Radovanovic (Revista Brasileira de Enfermagem)
ABSTRACT Objective: to evaluate the adherence and associate it to blood pressure control and to follow-up observation of people with hypertension in the Brazil’s Family Health Strategy. Method: cross-sectional study, conducted with 417 people in treatment of hypertension, living in a municipality located in the Northwest region of the state of Paraná, Brazil. The data were collected in the first 2016 semester, using an instrument adapted and validated for the evaluation of satisfaction with the services offered by Primary Health Care. Analysis of variance and the logistic regression model were used for the treatment of variables. Results: it was evidenced that people with inadequate follow-up observation evaluate the relations between professional/user and the guidance to the medications used as unsatisfactory. Conclusion: weak guidelines and ineffective dialogue between health professionals and users might result in an inadequate follow-up observation of blood pressure control and of people with hypertension.